2019
DOI: 10.1002/jgc4.1110
|View full text |Cite
|
Sign up to set email alerts
|

Men's experiences of recontact about a potential increased risk of prostate cancer due to Lynch Syndrome: “Just another straw on the stack”

Abstract: The practice of recontacting patients to provide new health information is becoming increasingly common in clinical genetics, despite the limited research to evidence the patient experience. We explored how men with Lynch Syndrome (LS) understand and experience being recontacted about a potential increased risk of prostate cancer. Sixteen men with LS (Meanage 51 years) were recruited from an Australian screening study to undergo a semi‐structured interview. A modified grounded theory approach was used to guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…In this study, patients showed a high interest in being recontacted. This is consistent with previous research exploring views of patients in clinical genetics (Carrieri et al, 2017;Dheensa et al, 2017;Griffin et al, 2007;Rasmussen et al, 2019;Romero Arenas et al, 2018). The preferred method for recontact in our study was personal letters containing information relevant to them, which is also found in other studies (Griffin et al, 2007;Rasmussen et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In this study, patients showed a high interest in being recontacted. This is consistent with previous research exploring views of patients in clinical genetics (Carrieri et al, 2017;Dheensa et al, 2017;Griffin et al, 2007;Rasmussen et al, 2019;Romero Arenas et al, 2018). The preferred method for recontact in our study was personal letters containing information relevant to them, which is also found in other studies (Griffin et al, 2007;Rasmussen et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…(2007). In an interview with 16 men with Lynch syndrome who were recontacted with information about a potentially increased risk for prostate cancer, participants reported a low level of emotional distress about being recontacted, and recontact was seen as desirable (Rasmussen et al., 2019). We found that more respondents reported reasons for not wanting recontact than there were respondents who actually did not want recontact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations